2013
DOI: 10.1200/jop.2013.001119
|View full text |Cite
|
Sign up to set email alerts
|

The National Cancer Institute–American Society of Clinical Oncology Cancer Trial Accrual Symposium: Summary and Recommendations

Abstract: Introduction: Many challenges to clinical trial accrual exist,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
118
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(120 citation statements)
references
References 149 publications
2
118
0
Order By: Relevance
“…Many factors weigh into low accrual, including trials available, sufficient clinical research staffing, and low accrual of minority populations. 71 Accrual of patients with metastatic breast cancer to early-phase trials is particularly low, despite data suggesting patients with metastatic TNBC enrolling in phase 1 trials may have improved survival outcomes. 72 Advances in tumor genetics have changed the landscape of how we treat breast cancer, and identifying targetable mutations may help select which drugs are more likely to have efficacy in specific intrinsic tumor types.…”
Section: Expanding Treatment Optionsmentioning
confidence: 98%
“…Many factors weigh into low accrual, including trials available, sufficient clinical research staffing, and low accrual of minority populations. 71 Accrual of patients with metastatic breast cancer to early-phase trials is particularly low, despite data suggesting patients with metastatic TNBC enrolling in phase 1 trials may have improved survival outcomes. 72 Advances in tumor genetics have changed the landscape of how we treat breast cancer, and identifying targetable mutations may help select which drugs are more likely to have efficacy in specific intrinsic tumor types.…”
Section: Expanding Treatment Optionsmentioning
confidence: 98%
“…Yet well under five percent of U.S. adult cancer patients are enrolled in cancer clinical trials [9, 10]. Increasingly numerous and stringent eligibility criteria represent a major barrier to clinical trial accrual [11, 12]. For instance, over 80 percent of lung cancer clinical trials sponsored or endorsed by the National Cancer Institute (NCI)-affiliated Eastern Cooperative Oncology Group (ECOG) exclude patients with prior cancer, resulting in exclusion of up to 18% of potential participants for this reason alone [13].…”
Section: Introductionmentioning
confidence: 99%
“…Stensland et al reported that 1 in 4 cancer clinical trials were stopped early with 1 in 10 being stopped for poor accrual [2]. Data are somewhat limited, but a panel of experts convened by the NCI and ASCO to discuss barriers to clinical trial enrollment in 2013 [3] cited barriers in three areas as most significant: 1) patient/community -2) physician/provider level -3) site/organizational. Physician/provider level barriers include willingness to refer a patient for study, lack of knowledge about available clinical trials and concern regarding a patient's ability to participate [3][4][5].…”
Section: Introductionmentioning
confidence: 96%
“…Data are somewhat limited, but a panel of experts convened by the NCI and ASCO to discuss barriers to clinical trial enrollment in 2013 [3] cited barriers in three areas as most significant: 1) patient/community -2) physician/provider level -3) site/organizational. Physician/provider level barriers include willingness to refer a patient for study, lack of knowledge about available clinical trials and concern regarding a patient's ability to participate [3][4][5]. Patient/community barriers have been noted to include being unaware of trial opportunities and complexity and stringency of the protocol [6] Both of these barriers could be addressed by providing a research registry to inform and match patients for study.…”
Section: Introductionmentioning
confidence: 99%